COVID-19 vaccines breakthrough infection and adverse reactions in medical students: a nationwide survey in Iran - Allahgholipour, Amirreza; Safavi-Naini, Seyed Amir Ahmad; Shekarriz Foomany, Zahra; Eskandari, Abdolvahab; Nazari Rostami, Hossein; Honarvar, Mohamad Javad; Mohammadi, Mohammad; Khalili, Parnian; Ilaghi, Mehran; Afshar, Hossein; Amini Baghbadorani, Ali; Moghimi, Hamid Reza; et al. (Frontiers in Public Health, 2024)
Introduction There are different types of COVID-19 vaccines approved worldwide. Since no national studies focus on vaccine-related adverse reactions and breakthrough cases, this study aimed to investigate the rate of adverse events and COVID-19 infection in medical students in Iran. Methods This retrospective cohort study included Iranian medical students who received two doses of COVID-19 vaccines. The medical team gathered the demographic characteristics, comorbidities, type of vaccine, adverse events following vaccination, and history of COVID-19 infection data through a phone interview. The frequency of adverse events and breakthrough infection was stratified by vaccine type (ChAdOx1-S, Gam-COVID-Vac, and BIBP-CorV). Results A total of 3,591 medical students enrolled in this study, of which 57.02% were females, with a mean age of 23.31 + 4.87. A PCR-confirmed and suspicious-for-COVID-19 breakthrough infection rate of 4.51 and 7.02% was detected, respectively. There was no significant relation between breakthrough infection and gender, BMI, blood groups, and comorbidities. However, there was a significant difference in breakthrough infection rate among different types of vaccines (p = 0.001) and history of COVID-19 infection (p = 0.001). A total of 16 participants were hospitalized due to COVID-19 infection after vaccination for reasons such as dyspnea, abnormal imaging, or decreased oxygen saturation. No severe infection or death was observed in the studied population. Conclusion Vaccination prevented severe COVID-19 infection, although a high breakthrough infection rate was evident among Iranian medical students during the Delta variant’s peak. Vaccine effectiveness may be fragile during emerging new variants and in high-exposure settings. Moreover, adverse events are rare, and the benefits of vaccination outweigh the side effects. However, many limitations challenged this study, and the results should be cautious.